2020
DOI: 10.1007/s10639-020-10340-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the blended learning model on preservice teachers’ academic achievements and twenty-first century skills

Abstract: The purpose of this study was to examine the effects of a blended teaching-learning approach on academic achievement and twenty-first century skills of preservice teachers who took the teaching principles and methods course. The implementation was carried out over a period of ten weeks with preservice teachers who were enrolled in pedagogical training at the Faculty of Education at Karamanoğlu Mehmetbey University in the 2019-2020 academic year. In the study, a semi-experimental research design with experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
4
26
0
6
Order By: Relevance
“…Despite the challenges, the satisfaction level of the participants about the blended learning model appears to be high as shown by the high ratings regarding the effectiveness of the model and its components and the advantages emphasized by the great majority outnumbering challenges. The findings of the study are therefore in line with several of the other blended learning studies on pre-service teacher education (Atmacasoy & Aksu, 2018;Caner, 2010;Monicka & Jayachithra, 2018;Scarlett, 2017;Senturk, 2020;Shand & Farrelly, 2017) as they in general show that blended learning has been perceived to be effective and resulted in participants' general satisfaction with variability of learning modes, materials and tasks accessible regardless of time and place and perpetual discussions on academic, professional and personal issues. Moreover, similar to those studies, in this study, blended learning has also displayed some hindrances.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Despite the challenges, the satisfaction level of the participants about the blended learning model appears to be high as shown by the high ratings regarding the effectiveness of the model and its components and the advantages emphasized by the great majority outnumbering challenges. The findings of the study are therefore in line with several of the other blended learning studies on pre-service teacher education (Atmacasoy & Aksu, 2018;Caner, 2010;Monicka & Jayachithra, 2018;Scarlett, 2017;Senturk, 2020;Shand & Farrelly, 2017) as they in general show that blended learning has been perceived to be effective and resulted in participants' general satisfaction with variability of learning modes, materials and tasks accessible regardless of time and place and perpetual discussions on academic, professional and personal issues. Moreover, similar to those studies, in this study, blended learning has also displayed some hindrances.…”
Section: Discussionsupporting
confidence: 86%
“…Blended learning has been applied and investigated in several pre-service teacher education courses. To illustrate, in Senturk (2020), which aimed to investigate the effects of a blended learning approach on academic achievement and twenty-first century skills of pre-service teachers via a semi-experimental research design, the model proved to be effective with a significant difference in favor of the experimental group. Similarly in their quasi-experimental study, Monicka & Jayachithra (2018) found that blended learning significantly increased the teaching competency of the teacher candidates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and have a high online learning capacity (Grande- de-Prado et al, 2020;Senturk, 2020;Reimers & Schleicher, 2020). Teachers must overcome all the problems that occur in online learning and teaching (Aliyyah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At this point, a series of skills conceptualized as "21 st century skills" emerges. According to the OECD, the 21 st century skills are defined as follows; collaboration, solving complex events, using technological tools, using language, symbols and texts (Ananiadou & Claro, 2009;Senturk, 2020). Schleicher (2012) list 21 st century skills as follows: critical thinking, creativity, problem-solving, decisionmaking and learning in the ways of thinking category; communication and collaboration in the ways of working category; information and communications technology (ICT) and information literacy in the tools for working category; and citizenship, life and career, personal and social responsibility in the category of skills for living in the world.…”
Section: St Century Skillsmentioning
confidence: 99%